Main-d'oeuvre immigrante et développement dualiste: l'économie canadienne au milieu du XIXe siècle - Seccareccia, Mario; Saint-Germain, Maurice (Histoire sociale / Social History, 2001)
Keywords: Britanniques

The Identification of Employment Centres in Canadian Metropolitan Areas: the Example of Montreal, 1996 - Coffey, William J.; Shearmur, Richard (The Canadian Geographer / Le Géographe canadien, 2001)

La ville, miroir et enjeu de la santé: Paris, Montréal et Alger au XXe siècle - Goubert, Jean-Pierre (Histoire, économie et société, 2001)
Keywords: Vaccination; Épidémies

Transmission culturelle aux enfants par de jeunes couples immigrants. Montréal, Québec, Sherbrooke - Helly, Denise; Vatz-Laaroussi, Michèle; Rachedi, Lilyane (Immigration et Métropoles, 2001)
Keywords: Enfants

L'évaluation d'une intervention: le travail de rue dans un organisme communautaire PACT de rue - Allaoui, Saandiya (Université du Québec à Montréal, 2001)
Keywords: Itinérance

"Identification des valeurs, des objectifs et des finalités actuels et souhaités de l'éducation chez les musulmans de la région de Montréal" - Aoui, Jamel (Université de Montréal, 2001)
Keywords: Musulmans

Les communautés religieuses et l'édition du manuel scolaire au Québec, 1765-1964 - Aubin, Paul (Groupe de recherche sur l'édition littéraire au Québec, 2001)
Keywords: Communautés religieuses; Enseignants; Édition

"Sur les berceaux je veille": les aides-maternelles de la Fédération nationale Saint-Jean-Baptiste et la professionnalisation des domestiques, 1928-1940 - Baillargeon, Denyse (Sextant, 2001)
Keywords: Domestiques; Fédération nationale Saint-Jean-Baptiste

“De la cathédrale au chantier!” Les intellectuels québécois et Vatican II (1963-1966) - Baillargeon, Gaëtan (Vatican II au Canada: enracinement et réception, 2001)
Keywords: Action nationale (L'); Cité Libre; Parti Pris; Relations (revue); Théologie; Évêques

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
Keywords: Noirs; Théâtre

La FTQ, ses syndicats et la société québécoise - Bélanger, Yves; Comeau, Robert; Métivier, Céline (Leaders du Québec contemporain, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Le monde social de la rue: expériences des jeunes et pratiques d'intervention à Montréal - Bellot, Céline (Université de Montréal, 2001)
Keywords: Itinérance

Les trajectoires des jeunes d'origine haïtienne dans le système québécois de protection de la jeunesse - Bernard, Léonel (Université de Montréal, 2001)
Keywords: Haïtiens

"L'impérieuse mission de la jeunesse" ou l'émergence d'un groupe social, la jeunesse - Bienvenue, Louise (Bulletin d'histoire politique, 2001)
Keywords: Action catholique

“Le Québec a charge d’âme”: l’Action française de Montréal et les minorités françaises (1917-1928) - Bock, Michel (Revue d'histoire de l'Amérique française, 2001)
En s'appuyant sur l'exemple de la revue mensuelle L'Action française, cet article cherche à circonscrire la place des minorités françaises du Canada dans le nationalisme canadien-français des années 1920, problématique négligée par les historiens. L'auteur démontre que la conception « romantique » qu'avait la revue de la nation canadienne-française faisait des minorités les vestiges ou le prolongement du grand « Empire français d'Amérique », argument qui sera fréquemment utilisé par la rédaction afin de revendiquer le respect de leurs droits scolaires et religieux. Par ailleurs, ce n'est que lorsque considérés en fonction des minorités françaises que quelques-uns des plus importants thèmes du nationalisme canadien-français, comme la mission providentielle du Canada français, trouvent tout leur sens. La nation étant une entité « organique », L'Action française assignait également au Québec un devoir de solidarité nationale envers les minorités aux prises avec les politiquesassimilatrices de la majorité anglo-protestante du pays.
Keywords: Action française (L'); Nationalisme

Catholicisme et nationalisme chez Lionel Groulx - Boily, Frédéric (Études canadiennes / Canadian Studies, 2001)
Keywords: Groulx, Lionel; Nationalisme

Le suicide dans le district judiciaire de Montréal (de 1815 à 1843 et de 1893 à 1903) - Bordeleau, François (Université du Québec à Montréal, 2001)
Keywords: Mortalité

Le mouvement communautaire haïtien de Montréal en tant que mouvement social - Boucard, Alix (Université de Montréal, 2001)
Keywords: Haïtiens

Plus que parfaites: un siècle de services domestiques à Montréal - Bourbeau, Amélie (Cap-aux-Diamants, 2001)
Keywords: Domestiques; Femmes

Michel Chartrand: l'évolution idéologique d'un contestataire québécois: 1936-2000: un parcours intellectuel marginal? - Bourgeois, Patrick (Université Laval, 2001)
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Crise d'octobre; Grèves; Socialistes

Ritual Knowledge, Virtual Analysis: Reading Vodou from the Inside Out - Boutros, Alexandra (Université Concordia, 2001)

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

L'expérience de la pratique de la danse salsa des jeunes adultes dans deux discothèques latines de Montréal: une participation à une culture, une rencontre, un rituel - Burelle, Édith (Université du Québec à Montréal, 2001)
Keywords: Danse; Latino-Américains

Histoire des écoles d'Hochelaga-Maisonneuve. Tome 1. L'École Notre-Dame-de-l'Assomption (Louis-Jolliet) - Cadotte, Robert; Noël, Colette (Commission scolaire de Montréal et Atelier d'histoire Hochelaga-Maisonneuve, 2001)
Keywords: Hochelaga (quartier); Maisonneuve; Quartiers

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

La FTQ et le Québec syndical - Clément, Carole; Fédération des travailleurs et travailleuses du Québec (Fédération des travailleurs et travailleuses du Québec, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Légitimité de l’apostolat de l’édition: Le Lévrier et Fides - Cloutier, Yvan (Études d'histoire religieuse, 2001)
Keywords: Fides; Édition

Les instituts Nazareth et Louis-Braille, 1861-2001: une histoire de cœur et de vision - Commend, Susanne (Septentrion, 2001)

Italian Immigrant Women and Literacy: A Case Study - Constantino, Patricia (Université Concordia, 2001)
Keywords: Femmes; Italiens

Tibetans in Québec: Proﬁle of a Buddhist Community - Cormier, Louis (Université du Québec à Montréal, 2001)
Keywords: Tibétains

Analyse de l'engagement organisationnel de professionnels œuvrant dans une institution universitaire québécoise - Côté, Ghislaine (Université du Québec à Montréal, 2001)
Keywords: Université du Québec à Montréal

La dynamique sociale entourant les jardins communautaires: l'individu, le groupe et le jardin. Le cas de Montréal - Daclon Bouvier, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Groupes populaires; Jardins

Le théâtre d'intervention et les jeunes de la rue - Dagenais, Bernard (Université du Québec à Montréal, 2001)
Keywords: Itinérance; Théâtre

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

La présence communiste au Québec (1929-1939) ou la présence de "l'homme au couteau entre les dents" - Dansereau, Bernard (Bulletin d'histoire politique, 2001)
Keywords: Communistes

Analyse comparative des politiques de logement en regard des problématiques et tendances récentes - Dansereau, Francine; Divay, Gérard; Aubrée, Loïc; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

Analyse comparative des politiques et interventions en habitation - Dansereau, Francine; Divay, Gérard; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie; Aubrée, Loïc (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Ces médecins montréalais en marge de l'orthodoxie - Desjardins, Rita (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2001)
Keywords: Médecine

Le renforcement des interventions gouvernementales dans le domaine de la santé entre 1922 et 1936: le Service provincial d'hygiène de la province de Québec - Desrosiers, Georges; Gaumer, Benoît (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2001)
Keywords: Enfants; Mortalité; Médecine; Tuberculose; Épidémies

Memory and Migration: Ethiopian Jews in Montreal - Djerrahian, Gabrielle (Université de Montréal, 2001)
Keywords: Africains; Juifs

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

La paroisse urbaine comme communauté sociale: l'exemple de Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (La paroisse, 2001)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

Jeunes filles affiliées aux gangs de rue à Montréal: cheminements et expériences - Fournier, Michèle (Université de Montréal, 2001)
Keywords: Criminalité; Délinquance

1920-2001, 81 ans de solidarité ouvrière - Fournier, Roseline; Houle, Louis-Serge (Conseil central du Montréal métropolitain, CSN, 2001)
Keywords: Confédération des syndicats nationaux; Conseil central des syndicats nationaux de Montréal

La pensée de Gustave Francq, syndicaliste et réformateur social: textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 2001)

Jules Gilbert: pionnier de l'éducation sanitaire - Gaumer, Benoît; Desrosiers, Georges (Célébrités / Collection biographique, 2001)
Keywords: Médecine; Université de Montréal

Le Musée de l'École des HÉC (1910-1956) - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2001)
Keywords: Expositions; Musées; École des hautes études commerciales

Le jeûne du ramadan en contexte de migration: le cas des immigrants d'origine marocaine à Montréal - Grégoire, Anne-Josée (Université de Montréal, 2001)
Keywords: Maghrébins; Marocains

L’Église catholique dans la société québécoise des années 1930 à 1970: du triomphalisme organisationnel à la recherche d’identité - Grégoire, Jean-Luc (Université de Sherbrooke, 2001)

Plus que parfaites: les aides familiales à Montréal, 1850-2000 - Groot, Raphaëlle de; Ouellet, Élizabeth (Remue-ménage, 2001)
Keywords: Domestiques; Femmes; Institut du Bon-Conseil

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

L'identité ethnolinguistique de jeunes adultes issus de couples mixtes francophones/anglophones à Montréal - Hadiri, Myriam (Université de Montréal, 2001)
Keywords: Anglophones; Francophones; Langue

Daniel Coussirat (1841-1907): la vie et l’œuvre d’un intellectuel franco-protestant - Hamelin, Charles (Université de Montréal, 2001)
Keywords: Protestants

L'éducation "idéale" dans un monde "idéal": le Dunham Ladies' College / St. Helen's School et l'élite anglicane du diocèse de Montréal (1870-1930) - Harbec, Marie-Ève (Université McGill, 2001)
Keywords: Anglicans

Dealing with "the Destitute and the Wretched": The Protestant House of Industry and Refuge in Nineteenth-Century Montreal - Harvey, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Keywords: Itinérance; Philanthropie; Protestants

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Le maternalisme, une solution féminine à la Crise? La réponse de la Fédération nationale Saint-Jean-Baptiste - Hébert, Karine (Bulletin d'histoire politique, 2001)
Keywords: Crise; Fédération nationale Saint-Jean-Baptiste

Origine et consolidation d'un réseau littéraire au XXe siècle: la réseau associé à la revue La relève - Houle, Nancy (Université de Sherbrooke, 2001)
Keywords: Relève (La); Écrivains

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

La dépression politique des Anglo-Montréalais lors de la crise des années trente - Jedwab, Jack (Bulletin d'histoire politique, 2001)
Keywords: Anglophones; Crise

From the Ghetto to the Main: the Story of the Jews of Montreal - King, Joe (Montreal Jewish Publications Society, 2001)
Keywords: Juifs

De prudence et d'audace. L'enseignement religieux en contexte de renouveau catéchistique chez les Frères des Écoles chrétiennes au Québec (1930-1940) - Lanouette, Mélanie (Études d'histoire religieuse, 2001)
Keywords: Communautés religieuses; Frères des écoles chrétiennes; Théologie

Les patronages des Religieux de Saint-Vincent de Paul: lieu de formation religieuse en milieu ouvrier, 1935-1955 - Lantagne, Caroline (Études d'histoire religieuse, 2001)
Keywords: Communautés religieuses; Saint-Vincent-de-Paul (Société)

Les communautés religieuses au Québec: pour une approche par familles spirituelles - Laperrière, Guy (Études d'histoire religieuse, 2001)
Keywords: Communautés religieuses

Guido Nincheri artiste entrepreneur - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Le vitrail au studio de Guido Nincheri - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Vitraux; Églises

Guido Nincheri muraliste - Laroche, Ginette; Pellissier, Pierlucio (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Églises

Perceptions linguistiques à Montréal - Laur, Elke (Université de Montréal, 2001)
Keywords: Langue

Appréhender la nation, vivre la diaspora regards arméniens - Lenoir-Achdjian, Annick (Université de Montréal, 2001)
Keywords: Arméniens

Des moyens de faire face: les syndicats internationaux et la crise des années trente - Leroux, Éric (Bulletin d'histoire politique, 2001)
Keywords: Crise; Syndicats internationaux

Gustave Francq: figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Éric (Études québécoises, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

La Vita e bella - Létourneau, Isabelle (Continuité, 2001)
Keywords: Petite-Italie (quartier); Quartiers

Réminiscences italiennes - Létourneau, Isabelle (Continuité, 2001)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

Cultural Sensitivity in the Context of Ethnic Polities: A Comparison of Two Families Service Agencies - Leung, Ho Hon (Université McGill, 2001)
Keywords: Chinois; Famille; Juifs

Groupes, identités et municipalités dans l’histoire de Montréal et de sa région - Linteau, Paul-André (Ministère des Affaires municipales et de la Métropole du Québec, 2001)

Libéralisme, nationalisme et catholicisme dans la pensée politique de Claude Ryan au Devoir (1962-1978) - Marcil, Olivier (Université de Montréal, 2001)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan, Claude

North of the Colour Line: Sleeping Car Porters and the Battle Against Jim Crow on Canadian Rails, 1880-1920 - Mathieu, Sarah-Jane (Saje) (Labour / Le travail, 2001)
Keywords: Chemins de fer; Noirs; Transport en commun; Travail

Le Montréal juif entre les deux guerres / Tsvishn tsvey velt milhomes - Medresh, Israël (Septentrion, 2001)
Keywords: Juifs

Les pratiques de gestion dans les PME de la communauté haïtienne de Montréal - Michel, Dicarmel (École des hautes études commerciales de Montréal, 2001)
Keywords: Haïtiens

‘Preach the World’: Canadian Imperialism and Missionary Outreach at the Montreal Diocesan Theological College, 1892-1903 - Mills, Sean (Journal of the Canadian Church Historical Society, 2001)
Keywords: Anglicans; Missions; Protestants; Théologie

Le transport à vélo: le cas des étudiants de l'Université du Québec à Montréal - Moran, Anne-Marie (Université du Québec à Montréal, 2001)
Keywords: Cyclisme; Université du Québec à Montréal; Étudiants

Deserting Daughters: Runaways and the Red Light District of Montreal before 1945 - Myers, Tamara (Child Welfare and Social Action: Nineteenth and Twentieth Centuries, 2001)
Keywords: Délinquance

The Historical Record and Adolescent Girls in Montreal’s Red-Light District - Myers, Tamara (Framing Our Past: Constructing Canadian Women’s History in the Twentieth Century, 2001)
Keywords: Enfants; Femmes; Prostitution

Retorts, Runaways and Riots: Patterns of Resistance in Canadian Reform Schools for Girls - Myers, Tamara; Sangster, Joan (Journal of Social History, 2001)
Keywords: Communautés religieuses; Délinquance; Enfants; Soeurs du Bon-Pasteur; Tribunaux

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal: le cas des Français, des Vietnamiens, des Libanais et des Haïtiens - Ndiaye, Sophie (Université du Québec à Montréal, 2001)
Keywords: Français; Haïtiens; Libanais; Vietnamiens

Benedict Labre House: 1952-1966: The History of an Unofficial Lay Apostolate - Nolan, Patricia A. E. (Université Concordia, 2001)

Entre les rues Coloniale et Saint-Urbain. Les Juifs ashkénazes dans les années 1930 - Olazabal, J.-Ignace (Bulletin d'histoire politique, 2001)
Keywords: Juifs

L'Église et l'édification d'une culture publique au Québec - Perin, Roberto (Études d'histoire religieuse, 2001)
Keywords: Bourget, Ignace; Évêques

Une jeunesse unique? Mouvements de jeunesse et contestation sociale - Piché, Lucie (Études d'histoire religieuse, 2001)
Keywords: Femmes; Jeunesse ouvrière catholique (JOC)

The Influence of Culture on Pro-Environmental Activities: Comparing English, French and Italian Canadians - Qian, Zhonglian Cindy (Université Concordia, 2001)
Keywords: Italiens

Parcours d’une collaboration: les intervenants psychiatriques et psychologiques à la Cour des jeunes délinquants de Montréal (1912-1950) - Quevillon, Lucie (Université du Québec à Montréal, 2001)
Keywords: Délinquance; Enfants; Psychologie; Tribunaux

Lieux et réseaux de sociabilité littéraire au Québec - Rajotte, Pierre (Nota bene, 2001)
Keywords: Clubs; Journalistes; Librairie; Écrivains; Édition

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
Keywords: Musique; Noirs

L'apport des services de proximité en matière de revitalisation socio-économique des quartiers - Rochefort, Michel (Université du Québec à Montréal, 2001)
Keywords: Quartiers

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

La Faculté de théologie de l'Université de Montréal: mémoire et histoire, 1967-1997 - Sauvé, Madeleine (Fides, 2001)
Keywords: Théologie; Université de Montréal

Du képi au kippa: implantation des nouvelles politiques de rapprochement du service de police de la Communauté urbaine de Montréal en milieu hassidique - Shamlian, Isabelle (Université du Québec à Montréal, 2001)
Keywords: Hassidim; Juifs; Police

Analyse des valeurs patrimoniales du site et des bâtiments de l'Oratoire Saint-Joseph du Mont-Royal - Tanguay, Caroline (2001)
Keywords: Oratoire Saint-Joseph; Patrimoine

Le rôle joué par le Conseil d’hygiène de la province de Québec dans la prévention de la variole de 1888 à 1922 - Therrien, Sébastien (Université de Sherbrooke, 2001)
Keywords: Mortalité; Médecine; Vaccination; Variole

L'étudiant idéal vers 1913 - Trépanier, Pierre (Les Cahiers des dix, 2001)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC); Groulx, Lionel; Étudiants

Chiniquy - Trudel, Marcel (Célébrités / Collection biographique, 2001)
Keywords: Chiniquy, Charles

HIV Risk Behaviour and Predictors of Initiation into Prostitution among Female Street Youth in Montreal, Canada - Weber, Amy E. (Université McGill, 2001)

The Practice and Meaning of Bonsai, Ikebana, and Tea in Montreal and Abroad: A Case Study of the Processes of Cultural Globalization - Wilson, Hayley (Université Concordia, 2001)
Keywords: Japonais

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme